Effects of exosomes on pre-metastatic niche formation in tumors - Yaxin Guo; Xiang Ji; Jinbo Liu; Dandan Fan; Quanbo Zhou; Chen Chen; Weiwei Wang; Guixian Wang; Haijiang Wang; Weitang Yuan; Zhenyu Ji; Zhenqiang Sun (Molecular Cancer, 2019)
Abstract A pre-metastatic niche is a microenvironment prepared for the colonization of circulating tumor cells in specific organs. Exosomes are extracellular vesicles with a variety of biological functions. Exosomes play an irreplaceable role in the development of pre-metastatic niches, and mainly function as communication medium. In this review, we analyzed the effects of exosomes on pre-metastatic niches from various perspectives, including inflammation, immune response, angiogenesis, organotropism, matrix remodeling and biomarker expression. In particular, exosomes express programmed death ligand 1 (PD-L1) and cause the immune escape of tumor cells. The immunomodulatory effects of exosomes and their potential in liquid diagnosis have drawn our attention. The potential value of exosomes and pre-metastatic niches will be realized in the field of immunity therapy.